Left-sided appendicitis due to anatomical variation: A case report - Hu, Qiang; Shi, Jianfeng; Sun, Yuanshui (Frontiers in Surgery, 2022)
Introduction Left-sided appendicitis is a rare condition, and we report a patient with left abdominal heterotopia of the right colon complicated by acute appendicitis in the left lower quadrant. Case presentation A 39-year-old male was admitted to hospital following left lower abdominal pain for 1 day. Imaging examination by abdominal CT showed that the appendix was not clearly seen, and a mass was found in the left lower abdomen. Because the patient's abdominal pain was severe and the current diagnosis was not clear, after soliciting the patient's consent, we performed laparoscopic exploration. This exploration revealed that the cecum and ascending colon were located in the left iliac fossa, the appendix was swollen, the length of the appendix was approximately 6 cm, the diameter of the appendix was approximately 1 cm, and there was pus moss attached to the surface. We performed a laparoscopic appendectomy; the procedure was uneventful and the patient was discharged 3 days after the procedure. Conclusion Left-sided appendicitis is a rare condition and is therefore easy to misdiagnose. Wrong diagnosis can lead to serious complications and endanger the patient's life. Therefore, a full combination of laboratory tests and CT scan is required. If still no diagnosis can be made correctly, a laparoscopic exploration needs to be performed in a timely manner. This case teaches us that when we encounter a patient with severe left abdominal pain that cannot be definitely diagnosed, we need to be vigilant and perform timely laparoscopic exploration when necessary.